Retraction note: CXCR2 mediates NADPH oxidase-independent neutrophil extracellular trap formation in cystic fibrosis airway inflammation - Marcos-Nickol, Veronica; Zhou-Suckow, Zhe; Yildirim, Ali Önder; Bohla, Alexander; Hector, Andreas; Vitkov, Ljubomir; Wiedenbauer, Eva-Maria; Krautgartner, Wolf Dietrich; Stoiber, Walter; Belohradsky, Bernd H.; Rieber, Nikolaus; Kormann, Michael; et al. (Nature medicine, 2011)
In the version of this article initially published, the authors reported that CXCL8 could efficiently induce neutrophil extracellular trap (NET) formation in vitro. When they followed up on the effect of recombinant CXCL8(IL-8) on NET formation by comparing different cell culture conditions and extending their studies to neutrophils obtained from a larger number of healthy blood donors, they found that the CXCL8 effect was donor dependent and was less robust than we previously thought.